"I don't think they're as culturally sensitive": a mixed-method study exploring e-mental health use among culturally diverse populations. (2nd January 2023) - Narayan, Shawna; Mok, Hiram; Ho, Kendall; Kealy, David
Abstract: Background: Culturally diverse populations (CDPs), such as visible minorities, face challenges, such as lack of culturally tailored resources, when accessing mental health services. These barriers may be addressed by e-mental health (eMH) technologies. However, little attention has been devoted to understanding the cultural responsiveness of these services among CDPs. Aims: This study explores CDPs experience of eMH for anxiety and depressive disorders in an urban area and gauge its cultural responsiveness. Methods: In this mixed methods study, participants ( N = 136) completed a survey regarding their eMH use, mental health status, and socio-demographic characteristics. Subsequently, participants ( N = 14) shared their experiences through semi-structured focus groups. Results: The majority of participants (68%) indicated that the eMH resources used were not culturally tailored. However, most participants (65%) agreed that the resource was available in their preferred language. Focus group discussions revealed key experiences around limited language diversity, cultural representation and cultural competency, and culturally linked stigma. eMH recommendations suggested by participants focused on including culturally tailored content, graphics and phrases, and lived experiences of CDPs. Conclusions: The findings showcase the need for more culturally responsive eMH beyond language translation, while providing healthcare professionals with a greater and nuanced understanding of treatment needs in cultural groups.